Drug Repurposing for Viral Infectious Diseases: How Far Are We? - Mercorelli, Beatrice (Trends Microbiol, 2018)
Despite the recent advances in controlling some viral pathogens, most viral infections still lack specific treatment. Indeed, the need for effective therapeutic strategies to combat ‘old’, emergent, and re-emergent viruses is not paralleled by the approval of new antivirals. In the past years, drug repurposing combined with innovative approaches for drug validation, and with appropriate animal models, significantly contributed to the identification of new antiviral molecules and targets for therapeutic intervention. In this review, we describe the main strategies of drug repurposing in antiviral discovery, discuss the most promising candidates that could be repurposed to treat viral infections, and analyze the possible caveats of this trendy strategy of drug discovery.